Financial Thought Innovations During the Time of Umar bin Khattab - Wajdi, Salman; Agung Ay, Rina Asmara (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
The new resources that flowed into the Islamic state during the era of the Rightly-Guided Caliphs revealed the beginnings of the cultural response between the new Islamic era and the civilizations of the conquered countries in the field of financial organization and laid the foundations for this response. Likewise, Caliph Omar ibn al-Khattab, whose actions in that direction represented a fundamental rule alongside the financial regulations of the Noble Messenger - may God bless him and grant him peace - which all Muslim Caliphs committed to after him. We conducted a literature study using a qualitative approach and descriptive interpretation. We found that this Caliph - Omar bin Al-Khattab - may God Almighty be pleased with him - aimed to save the people of the conquered countries from the injustices and heavy financial troubles they had previously suffered and, at the same time, to work to provide the emerging state with the resources that would achieve its political, economic, and military demands as well. Caliph Omar bin Al-Khattab relied on solving this new equation. What is the equation in this? The equation is that the Islamic State wants money to spend on its many needs while at the same time not wronging those people from whom these financial resources are taken.